"Téchne" y sus derivados y compuestos en la comedia griega - Sanchis Llopis, Jordi, 1957-; López Férez, Juan Antonio, 1940- (Madrid: Ediciones Clásicas, 2004)
From the second hatf of the V century B.C. there was a surge in the development of technology in the Greek world, which brought on the appearance of professions, disciplines and sciences. This gave rise to a wealth of literature by experts in these fields. At the same time, theories and thoughts on the concept and nature of techne were developed. Greek comedy, the development of which, to a great extent, occurred at the same time, makes reference to the practical, everyday experience of trades and arts in society and intellectual thought on it from a comic angle. Numerous comical passages and fragments contain the noun techne, and its different derivations and compounds. In comical texts one may find the ardent defence of certain trades, either real or the product of a witty mind, including themes which are common in the "technical" literature, or reflexions of a gnomic character on the nature of the tee/me, with regard to its advantages or disadvantages.
Keywords: Teatro griego; Comedia